2018
DOI: 10.1101/397802
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Solitary bee larvae prioritize carbohydrate over protein in parentally provided pollen

Abstract: 10 1. Bees, important pollinators, have declined significantly in recent decades, and human-11 induced changes to nutritional landscapes are partly responsible. Changes to nutritional 12 quality rather than quantity have been overlooked as a threat to bee health. Yet 13 knowledge of bee nutrition is currently largely restricted to adults of social species. 14 Larval stages, where most growth occurs, are relatively understudied -perhaps because 15 most social bees provision progressively and collectively, makin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 154 publications
(152 reference statements)
1
8
0
Order By: Relevance
“…Not all plants produce pollen of sufficient nutritional quality to meet the requirements of bees (Filipiak, 2017a,b). Since bee larvae require specific nutrients for growth and development (Austin & Gilbert 2018), large quantities of food can not compensate for poor quality (Filipiak, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Not all plants produce pollen of sufficient nutritional quality to meet the requirements of bees (Filipiak, 2017a,b). Since bee larvae require specific nutrients for growth and development (Austin & Gilbert 2018), large quantities of food can not compensate for poor quality (Filipiak, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This finding highlights the importance of crop species and flower timing in providing B. terrestris with adequate food resources in intensively managed agricultural systems. At a specific nutrient level, it was found that carbohydrate regulation was the most important variable in maximizing O. bicornis body size and survival, where the larval pupation occurred only after ingesting a fixed quantity of carbohydrates, but variable amounts of protein [118]. The authors of this study propose that the wide range in larval protein consumption is a result of their dependence on maternal nest provisioning for obtaining protein, and hence explains O. bicornis vulnerability to changes in landscape floral composition.…”
Section: Habitat Destruction and Fragmentationmentioning
confidence: 99%
“…Solitary bees also have similar nutritional requirements, for which most studies suggest that a departure from monoculture plantings is the best remedy [118,145,146,147]. For example, a range of seven to 1100 flowers or 0.9 to 4.5 flower heads is required to rear a single larva of 41 European bee species, depending on both species and host plant [148].…”
Section: Monoculture Plantingsmentioning
confidence: 99%
“…Bees meet all their nutritional demands via pollen and nectar collected from flowers (their main source of protein and carbohydrate respectively), and unlike the nymphs and larvae of traditional models of insect nutrient regulation, such as locusts and caterpillars, bee larvae are entirely dependent on the provisioning choices of adult bees. This means bee larvae likely have very little opportunity to selectively regulate their intake of nutrients (but see Austin and Gilbert, 2018). Honeybees are unique among bees in that in-hive nurse bees process the pollen and nectar brought back to the nest by foragers, and convert it to a nutritional substance known as royal jelly which they then regurgitate for larvae (Wright, Nicolson and Shafir, 2018).…”
Section: Introductionmentioning
confidence: 99%